2010
DOI: 10.1152/physrev.00012.2009
|View full text |Cite
|
Sign up to set email alerts
|

The Ventilatory Response to Hypoxia in Mammals: Mechanisms, Measurement, and Analysis

Abstract: The respiratory response to hypoxia in mammals develops from an inhibition of breathing movements in utero into a sustained increase in ventilation in the adult. This ventilatory response to hypoxia (HVR) in mammals is the subject of this review. The period immediately after birth contains a critical time window in which environmental factors can cause long-term changes in the structural and functional properties of the respiratory system, resulting in an altered HVR phenotype. Both neonatal chronic and chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
341
3
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(362 citation statements)
references
References 838 publications
14
341
3
4
Order By: Relevance
“…Serial sections demonstrated the expression of GSNOR and nNOS in neurons within the brainstem ( Figure 1A). Moreover, both proteins were seen in neurons located in the NTS, a region of the brain known to be involved in respiratory control (2,4). Immunofluorescence studies demonstrated that a subset of neurons contained both GSNOR and nNOS ( Figure 1B).…”
Section: Gsnor Is Present In Neurons Within the Brainstem Of Female Micementioning
confidence: 98%
See 2 more Smart Citations
“…Serial sections demonstrated the expression of GSNOR and nNOS in neurons within the brainstem ( Figure 1A). Moreover, both proteins were seen in neurons located in the NTS, a region of the brain known to be involved in respiratory control (2,4). Immunofluorescence studies demonstrated that a subset of neurons contained both GSNOR and nNOS ( Figure 1B).…”
Section: Gsnor Is Present In Neurons Within the Brainstem Of Female Micementioning
confidence: 98%
“…Hypoxia increases minute ventilation (VM) by activation of carotid body chemoafferents and integration of these signals by brainstem structures, including the nucleus tractus solitarius (NTS) (1)(2)(3)(4). The neurochemical mechanisms mediating the initial increase in VM upon exposure to hypoxia include: (1) activation of N-methyl-D-aspartate (NMDA) receptors (NMDARs); (2) increased activity of neuronal nitric oxide synthase (nNOS) via NMDAR-induced increases in intracellular Ca 21 ; and (3) activation of phospholipase C, protein kinase (PK) C, and tyrosine kinase phosphorylation cascades (3,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological response to whole-body hypoxic stress, observed for example at altitude, in pulmonary diseases, and in respiratory control disorders that commonly present during sleep, includes the archetypal reflex cardiorespiratory adjustments of increased ventilation (serving to better oxygenate the pulmonary blood), increased cardiac output (improving oxygen delivery to the systemic circuit), and systemic vasodilatation (enhancing local delivery and uptake of oxygen into peripheral tissues) that together protect against profound oxygen deficiency in the face of global hypoxic stress (Teppema and Dahan, 2010;Prabhakar and Semenza, 2012).…”
Section: Commentarymentioning
confidence: 99%
“…However, the mechanisms by which organisms detect hypoxic conditions can vary significantly (Taylor et al 1999). In mammals, respiratory control appears to be primarily internalised, with oxygen sensors located in the branches of the carotid arteries and the aortic arch (Lopez-Barneo et al 2010, Teppema & Dahan 2010, and carbon dioxide levels are monitored in the cerebrospinal fluid (Teppema & Dahan 2010). But because oxygen levels are fairly constant in environments for air-breathing animals, carbon dioxide receptors that measure the internal levels of this gas are of greater significance (Taylor et al 1999).…”
mentioning
confidence: 99%